Growth and differentiation of bone marrow hematopoietic cells in mice bearing Ehrlich ascite tumor and treated with Dicyclopentadienildichiorotitanium (IV) - Valadares, M. C.; Klein, S. I.; Zyngier, S.; Queiroz, MLS (Elsevier B.V., 1998)
In this work we have:investigated the growth and differentiation of bone marrow stem cells in mice bearing Ehrlich ascites tumor-and treated with three dose-regimens of Dicyclopentadienyldichlorotitanium (IV) (DDCT). We also: studied the presence of colony stimulating factors In the serum of PDCT-treated animals as well-as the effects-of the drug on the survival of the tumor-bearing mice. The-results demonstrated that the myelosuppression developed in the tumor-bearing animals is prevented by the administration:of 1, 2 or 3 doses of 15 mg/kg DDCT. In the treatment with three doses, however, 23 % of the animals died. Moreover, DDCT treatment in normal animals resulted in increased numbers of CFU-GM. We observed the presence of stimulating factors in the serum of drug-treated animals which induced the growth and differentiation of bone marrow progenitor cells from normal animals in vitro. on the other hand, in vitro addition of the drug to these cultures had no effect. Thus, we conclude that the drug protects against the myelosuppression induced by the tumor and that this protection may be related to an indirect action of the drug. (C) 1998 International Society for Immunopharmacology. Published by Elsevier B.V. Ltd.
Keywords: Ehrlich ascites tumor; hematopoietic cells; myeloprotection; titanocene; antitumor